Seroprevalence of some Infectious transboundry diseases in cattle imported from Sudan to Egypt - Hekal, Sahar Hussein Abdalla; Gaabary, Magdy Hassanein Al; Sayed, Magdy Mahmoud El; Mohamed Sobhy, Hassan; Fayed, Adel Abdul Azim (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Animal trade has an important role in the economy but in contrast, it causes the spread of infectious diseases overall the world, in particular, the trans-boundary animal diseases. Therefore, the aim of this study is to report the prevalence rate of some transboundary infectious diseases to assess the effectiveness of quarantine measure in the detection of exotic disease and clarify the role of live animal trade in infectious transboundary diseases spread. Materials and Methods: The study was done on 176 serum samples obtained from cattle imported from Sudan in order to determine the prevalence of foot and mouth disease (FMD), Peste Des Petits Ruminants (PPR), and Infectious Bovine Rhinotracheitis (IBR). Three serological tests were used; Serum neutralization test for FMD, Indirect enzyme-linked immunosorbent assay (i-ELISA) for PPR, and Competitive ELISA for IBR. Results: The seroprevalence of FMD in tested sera was; 77.27% in the serotype A (A-Iran), 68.18% in the serotype A (A-Africa), 93.82% in the serotype O (O-Pan Asia), and 35.227% in the serotype South African Territories-2 (SAT-2) SAT-2. While the overall seroprevalence of PPR was 49.431% and the IBR was 93.75%. Conclusion: The result indicates the serious role of live animal trade as “hubs” for infectious diseases spread. Subsequently, the common control measures must be taken to avoid the spread of the diseases through the animal trade; which include screening, surveillance, precautions at borders, and vaccination. J. Adv. Vet. Anim. Res., 6(1): 92-99, March 2019